COST PERFORMANCE ANALYSIS AND TIME DEVELOPMENT CONSTRUCTION PROJECT BRIDGE CHAIN KARANGGENENG NAWACITA CS USING THE EARNED VALUE METHOD - Bobby Damara (U Karst, 2020)
Cost, quality, and time are mandatory targets of construction management; project work can be said to be successful if triple constants cost, quality, and time the construction work of the Karanggeneng Nawacita Cs Suspension Bridge is a JUDESA project APBN project and has a period of 19 weeks working days with a budget of Rp 8.213.826.000, in the process of implementing the bridge construction, it is not free from several technical and non-technical constraints, the method earned value in this study used to determine Early Warning and integrate the concept of time and cost from the method, it earned value can be seen the progress and performance of the project with SV, CV, SPI, CPI, ECD, and EAC, from this study the results obtained ETC Rp 3.322.492.617. ETS review of the 14th week is 39 days, and to complete the project is EAC greater than Rp 82.137.617 of contract costs. While completing the project, EAS is 137 days, requiring additional work time for 12 days. Based on the results of the analysis conducted by the service provider must take appropriate fast action to avoid excessive over budget